2003
DOI: 10.1165/rcmb.2003-0060oc
|View full text |Cite
|
Sign up to set email alerts
|

House Dust Mite Der p 1 Downregulates Defenses of the Lung by Inactivating Elastase Inhibitors

Abstract: House dust mites (HDM) are the most common source of aeroallergens and in genetic susceptible individuals can cause symptoms ranging from atopic dermatitis to bronchial asthma. Der p 1, a major target of the human immune responses to HDM, through its enzymatic properties can modulate the adaptive immune system by the cleavage of CD23 and CD25. The consequences of this would be to promote allergic inflammatory responses. Furthermore, by disrupting epithelial tight junctions Der p 1 facilitates the transport of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 49 publications
0
70
0
Order By: Relevance
“…We emphasize that complete inactivation of the proteolytic activity is critical for elimination of the in vivo IgE-eliciting activity on the basis of our observations that E-64 treatment was not able to erase IgE-eliciting activity when the reactions were conducted with lower concentrations of E-64 and rDer p 1 (our unpublished observations), which is considered to decrease the probability of molecular collisions between E-64 and Der p 1 and to decelerate the speed of formation of E-64-rDer p 1 complexes. The cysteine protease activity of the house dust mite group 1 allergens has been reported to cleave some cell surface molecules (22-24, 26 -28) and protease inhibitors (25,26,28,30) and to modulate functions of various types of cells (21,22,27,(31)(32)(33)(34)(35)(36)(37)(38)(39). E-64-treated rDer p 1 with no proteolytic activity is considered to lose such activities and, in the present study, actually exhibited a remarkable reduction in Ab-eliciting activity.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…We emphasize that complete inactivation of the proteolytic activity is critical for elimination of the in vivo IgE-eliciting activity on the basis of our observations that E-64 treatment was not able to erase IgE-eliciting activity when the reactions were conducted with lower concentrations of E-64 and rDer p 1 (our unpublished observations), which is considered to decrease the probability of molecular collisions between E-64 and Der p 1 and to decelerate the speed of formation of E-64-rDer p 1 complexes. The cysteine protease activity of the house dust mite group 1 allergens has been reported to cleave some cell surface molecules (22-24, 26 -28) and protease inhibitors (25,26,28,30) and to modulate functions of various types of cells (21,22,27,(31)(32)(33)(34)(35)(36)(37)(38)(39). E-64-treated rDer p 1 with no proteolytic activity is considered to lose such activities and, in the present study, actually exhibited a remarkable reduction in Ab-eliciting activity.…”
Section: Discussionmentioning
confidence: 64%
“…The cysteine protease activity of Der p 1 and Der f 1 has been suggested to be involved in the pathogenesis of allergies by facilitating the passage of their own and other allergens across the epithelium (21,22), cleaving and/or interacting with cell surface molecules and intrinsic protease inhibitors (23)(24)(25)(26)(27)(28)(29)(30), and modulating the function of various cells (23,27,(31)(32)(33)(34)(35)(36)(37)(38)(39). Herbert et al (21) speculated that cysteine protease activity of natural Der p 1 could be activated in vivo by glutathione in the airway on the basis of their in vitro observations.…”
mentioning
confidence: 99%
“…5 Several reports indicated that Der p 1 is able to increase bronchial permeability by disruption of the intercellular tight junctions and cleavage of the α1-antitrypsin serine protease inhibitor. 6,7 Furthermore, Der p 1 is capable of cleaving receptors, including the IgE low-affinity receptor (CD23) present at the surface of plasmocyte cells, the α-subunit of the interleukin-2 receptor (CD25) of T cells and the CD40 of dendritic cells. 5,[8][9][10][11] All these processes favor the development of the allergic response; thus, the development of specific Der p 1 inhibitors is of considerable interest.…”
Section: Introductionmentioning
confidence: 99%
“…Cysteine protease activity of our preparations of rDer p 1 and rDer f 1 also crucially commits to the sensitization process in mice (37). Although Phillips et al (60) reported that Der p 1 stimulated purified human basophils to release IL-4, whether its cysteine protease activity is responsible for the basophil activation is unknown because their Der p 1 preparation also contained serine proteases other than Der p 1 (28,61). Whether the rDer f 1 and rDer p 1, which show cysteine protease activity but no serine protease activity (15), could stimulate basophils to produce Th2-inducing cytokines should be addressed in a future study.…”
Section: Discussionmentioning
confidence: 87%
“…It has been proposed that the proteolytic activity of Der f 1 and Der p 1 is involved in the pathogenesis of allergies and sensitization to the production of IgE by reducing physical and biochemical tissue barriers, cleaving various molecules, and modulating the functions of various cells (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). Cystatin A is the dominant biochemical skin barrier that eliminates the enzymatic activity of these mite cysteine proteases and prevents them from stimulating keratinocytes (31,40).…”
Section: Discussionmentioning
confidence: 99%